Spatial distribution and species composition of small pelagic fishes in the Gulf of California - Edgar Lanz; Manuel O Nevárez-Martínez; Juana López-Martínez; Juan A Dworak (Revista de Biología Tropical, 2008)
Traditional regionalization methods in fisheries based on provinces or major fishing areas, includes large and arbitrary grids in which basic statistics or inferences on distribution or abundance are made. We describe a method for regionalization and analysis of fishing activities for small pelagic fisheries in the Gulf of California based on spatial patterns of landing and catch data in a Geographic Information System (GIS) environment. A fisheries database from logbooks with spatial attributes from October 2002 to June 2007 was analyzed. Landings and catching data were transformed to a Weighted Region Index (WRI) by using fuzzy logic operators. The WRI revealed fishing action centers characterized by areas with the highest WRI values, and a hierarchy for the relative importance of the regions was established. Guaymas, Desemboque de Caborca, Isla Patos, and Bahía San Rafael they were the most prominent ones. An analysis of the relative frequency of species composition showed that the Pacific sardine had an over 80 % abundance in the midriff islands, and remained as the most important in the upper gulf regions, while in the central part of the gulf, relative abundances of Pacific sardine and Northern anchovy were more balanced. Relative abundance of mackerel was significantly larger around Isla Patos than in any other place. Guaymas had the largest relative composition of Northern anchovy and the lowest values for Pacific sardine. Desemboque de Caborca showed the largest homogeneity in species relative composition. It is important to highlight that this results come from in situ data, while the results previously reported come from landing statistics by port. Therefore, the present method acknowledges the spatial differences of species by regions, additional to the traditional time series analysis. Rev. Biol. Trop. 56 (2): 575-590. Epub 2008 June 30. Los métodos tradicionales de regionalización en pesquerías, basados en provincias o grandes regiones, incluyen áreas arbitrarias y homogéneas sobre las cuales se realiza estadística básica o inferencias relacionadas con la distribución y la abundancia de estos recursos. El presente trabajo describe una metodología para la regionalización y el análisis de la actividad pesquera de pelágicos menores en el Golfo de California basado en los patrones espaciales de la información de lances y capturas utilizando herramientas de Sistemas de Información Geográfica (SIG). La información pesquera, con atributos espaciales, provino de bitácoras de pesca para el periodo comprendido de octubre 2002 a junio 2007. Los datos de lances y capturas fueron transformados a un Índice de Región Ponderada (WRI) utilizando operadores de lógica difusa. El WRI reveló centros de actividad pesquera caracterizados por áreas con los valores más altos de WRI y se obtuvo un orden jerárquico para denotar la importancia relativa de cada región, siendo las regiones de Guaymas, el Desemboque de Caborca, Isla Patos y Bahía San Rafael, los más prominentes. El análisis de la frecuencia relativa de la composición de especies mostró que la sardina Monterrey tuvo una abundancia relativa mayor al 80% en la región de las Grandes Islas y permaneció como la especie más importante en las regiones del alto golfo, mientras que en la parte central del golfo las abundancias de la sardina Monterrey y la ancho-veta norteña estuvieron más equilibradas. La abundancia relativa de la macarela fue significativamente mayor en la región de la Isla Patos, respecto a cualquier otra región. La región de Guaymas mostró la mayor composición relativa de anchoveta norteña, en contraste con los más bajos valores de sardina Monterrey. El Desemboque de Caborca mostró la mayor homogeneidad en la composición relativa de especies. Estos resultados provienen de datos in situ, mientras que los resultados previamente reportados provienen de estadísticas de lances por puerto. En consecuencia, el presente método reconoce las diferencias espaciales en la composición de especies por regiones (adicionales a los tradicionales análisis de series de tiempo).